EFL Students’ Interpretation of Implicature and Gender Representation in Memes - Nugroho, Ardi; Liemantara, Kevin Nathanael (Journal of English Teaching, Literature, and Applied Linguistics, 2024)
The purpose of this study is to examine how EFL students interpret implicature in memes, more specifically those that contain gender representation. A total of 30 undergraduate students majoring in English were used as the respondents. They were asked to fill out a questionnaire containing 7 memes which contain representations of men and women. Considering that memes are multimodal constructions as they are commonly made up of a combination of texts and images, the interaction between these two were also investigated to see how they were able to assist the students in interpreting the hidden meaning behind the memes. The findings revealed that a lot of the students were unable to properly deduce or comprehend the implied meaning regarding gender representation even though they felt that the texts and images did indeed help them in understanding the memes. It was found that they mostly interpreted the memes explicitly. This shows that they still lack pragmatic competence overall. Therefore, it was suggested that language teachers pay more attention to the teaching of implicatures, especially in memes.